NIR-light-activated combination therapy with a precise ratio of photosensitizer and prodrug using a host-guest strategy - Chen, Hongzhong (2020)
The co-delivery of photosensitizers with prodrugs sensitive to reactive oxygen species (ROS) for light-triggered ROS generation and cascaded prodrug activation has drawn tremendous attention. However, the absence of a feasible method to deliver the two components at a precise ratio has impaired the application potential. Herein, we report an efficient method to produce a nanosized platform for the delivery of an optimized ratio of the two components by the means of host–guest strategy for maximizing the combination therapy efficacy of cancer treatment. The key features of this host–guest strategy for the combination therapy are that the ratio between photosensitizer and ROS-sensitive prodrug can be easily tuned, near-infrared (NIR) irradiation can sensitize the photosensitizer and activate the paclitaxel prodrug for its release, and the accumulation process can be tracked by NIR imaging to maximize the efficacy of photodynamic and chemotherapy.